Coefficient Estimates for Subclasses of Regular Functions - Juma, Abdul Rahman S.; Saloomi, Mohammed H. (Iraqi Journal of Science, 2018)
The aim of this paper is to introduce and investigate new subclasses of regular functions defined in . The coefficients estimate and for functions in these subclasses are determined. Many of new and known consequences are shown as particular cases of our outcomes.